Fear of Tooth Extraction among Patients Visiting a Tertiary Care Center - Gurung, Gopal; Pokharel, Mona; Thapa, Sabana; Parajuli , Asmita (Birat Journal of Health Sciences, 2024)
Introduction: Extraction of teeth is the most commonly performed procedure in dentistry. Extraction of teeth is known to be in the top five most frightening procedures in dental practice. Objectives: To find out the prevalence of fear of tooth extraction, its association with gender, age, education, and previous extraction experience, and ranking of the fear of tooth extraction. Methodology: A descriptive cross-sectional study was conducted among the patients visiting the Department of Dental Surgery at Birat Medical College and Teaching Hospital for the extraction of teeth from 1st March 2023 to 31st August 2023. Results: Out of 278 patients, 219 (78.70%) patients had a fear of tooth extraction. Gender wise 153 (85%) females and 66 (67.3%) males had a fear of tooth extraction. Fear of tooth extraction was highest in the age group of 18-27 years (n= 67; 87.01%). The prevalence of fear of extraction among previous extraction patients was 106 (69%) and 113 (90.4%) in non-extraction patients. The association of fear of tooth extraction with gender, age, and experience of previous extraction was found to be significant (p<0.05) using the Chi-square test. The association of fear of extraction of a tooth with the level of education was found to be not significant (p>0.05). While ranking the fear of extraction by patients, the first (most feared) was pain during extraction (n=134; 61.20%). Conclusion: The fear of extraction of teeth was seen in the majority of patients and was more prevalent in females, younger patients, and previous non-extraction patients.